2012
DOI: 10.1186/1471-2180-12-284
|View full text |Cite
|
Sign up to set email alerts
|

Putative SF2 helicases of the early-branching eukaryote Giardia lamblia are involved in antigenic variation and parasite differentiation into cysts

Abstract: BackgroundRegulation of surface antigenic variation in Giardia lamblia is controlled post-transcriptionally by an RNA-interference (RNAi) pathway that includes a Dicer-like bidentate RNase III (gDicer). This enzyme, however, lacks the RNA helicase domain present in Dicer enzymes from higher eukaryotes. The participation of several RNA helicases in practically all organisms in which RNAi was studied suggests that RNA helicases are potentially involved in antigenic variation, as well as during Giardia differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 91 publications
(105 reference statements)
0
3
0
Order By: Relevance
“…This is insofar interesting as this enzyme catalyzes the complete reduction and thus inactivation of nitro compounds in functional assays and in E. coli ( Müller et al, 2013 , 2015 ) and would therefore be a suitable candidate for up-regulation in resistant strains. Since the corresponding gene is transcribed in all strains ( Müller et al, 2013 ), either the mRNA is subjected to post-transcriptional gene silencing, most likely by RNA interference ( Prucca and Lujan, 2009 ; Gargantini et al, 2012 ) or the corresponding polypeptide is quickly degraded. We have performed immunoblots with specific antisera raised against two unique peptides of NR2 and could not detect a corresponding signal in G. lamblia trophozoite crude extracts (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This is insofar interesting as this enzyme catalyzes the complete reduction and thus inactivation of nitro compounds in functional assays and in E. coli ( Müller et al, 2013 , 2015 ) and would therefore be a suitable candidate for up-regulation in resistant strains. Since the corresponding gene is transcribed in all strains ( Müller et al, 2013 ), either the mRNA is subjected to post-transcriptional gene silencing, most likely by RNA interference ( Prucca and Lujan, 2009 ; Gargantini et al, 2012 ) or the corresponding polypeptide is quickly degraded. We have performed immunoblots with specific antisera raised against two unique peptides of NR2 and could not detect a corresponding signal in G. lamblia trophozoite crude extracts (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A comparative genomic analysis of both Trypanosoma genomes showed that they display high levels of synteny and share a conserved set of approximately 6,200 genes [ 19 ]. Recently, Gargantini et al [ 20 ] identified a total of 103, 112, and 113 putative helicases in L. major , T. brucei , and T. cruzi genomes, respectively, from an extensive search in the TriTryp database. Interestingly, most predicted proteins are DEAD/DExH-box helicases with 27-30 members in the 3 species [ 15 ].…”
Section: Protozoan and Nematode Parasites Have Large Dead/dexh-box Rnmentioning
confidence: 99%
“…It has mitochondrial organelles called mitosomes [ 22 ] and 2 nuclei that contain 1.2×10 7 bp of DNA with a GC content of 46% [ 23 ]. From BLAST analyzes using the human eIF4A and DHX8 amino acid sequences as DEAD-box and DExH-box helicase prototypes, respectively, Gargantini et al [ 20 ] identified a set of 32 putative RNA helicases, including 22 DEAD-box and 6 DEAH-box proteins. G. lamblia proteins present high sequence similarity with characterized human and yeast homologs, which suggests that they may have a similar function in RNA metabolism.…”
Section: Protozoan and Nematode Parasites Have Large Dead/dexh-box Rnmentioning
confidence: 99%